Geological Structure and Perspectives of Oil and Gas Bearing in Neogene Sediments of the Southern Part of the Kuril Island Arc System - Krikun Nikita Sergeevich; Babenko I. A.; Talovina Irina V.; Duryagina Asiya M. (Russian Journal of Earth Sciences, 2024)
The article reviews the current state of knowledge about the geological structure and oil and gas bearing of the Southern Kurils, supplemented by the results of the authors’ own observations. Expansion of the mineral resource base of remote regions plays an important role for its economic development. The oil and gas content of the Southern Kurils is a subject of debate. Based on the analysis of the data accumulated and obtained by the authors, the geological structure of the southern islands of the Greater Kuril Ridge has been clarified. The Upper Miocene-Pliocene complex has been identified in potentially oil and gas bearing Neogene sediments on the basis of direct and indirect signs, in which lithological and structural traps may be formed. As a result of comparative analysis of prospective deposits of onshore, offshore areas of the Mid-Kurilsk Trough and adjacent objects of the North-West Pacific, rocks of the basement of the island arc are assumed to be oil and gas bearing. The most perspective areas from the point of view of oil and gas potential onshore and offshore have been identified, which are the Kuibyshev Block, Iturup Island, and Kasatka Bay, respectively.